Management of Le Fort III Fracture: A Case Report and Review of Maxillofacial Surgical Treatment - Zam, Syarifa Nova Amiza; Reza, Faizal (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Maxillofacial trauma is a common occurrence, with midface fractures being serious injuries requiring thorough evaluation and appropriate management. Le Fort III fractures involve multiple fractures of the zygomatic bone, orbit, nasal bones, maxillary sinuses, and nasal septum. Case Report: A 36-year-old male presented to the emergency department of SULTAN FATAH Hospital, Demak, Indonesia with facial injuries following a traffic accident. The patient exhibited facial swelling, raccoon eyes, persistent nasal bleeding, and difficulty opening his mouth. A CT scan confirmed a Le Fort III fracture. Management included stabilization of the zygomaticomaxillary articulation, fracture segment repositioning via a gingivobuccal incision, and fixation with miniplates and screws. Discussion: The leading causes of maxillofacial fractures include traffic accidents, falls, physical assaults, sports injuries, and occupational hazards. The management of Le Fort III fractures involves early stabilization, anatomical reduction, and immobilization to ensure optimal recovery. Repositioning and fixation with miniplates and screws are essential for maintaining facial stability and occlusal function. Conclusion: Midface fractures require a comprehensive evaluation and appropriate treatment. This case highlights the importance of imaging for diagnosing Le Fort III fractures and the role of surgical intervention in restoring facial structure and function.